Effects of dietary star anise () supplementation during late gestation and lactation on the performance of multiparous sows and their progeny until 21 days post-weaning - Jeong Hyun Moon; Jae Cheol Jang; Minsoo Park; Yoo Yong Kim (Animal Bioscience)
Objective This study aimed to investigate the effects of star anise (SA) supplementation during late gestation and lactation on the performance of multiparous sows and their progeny until 21 days post-weaning. Methods A total of forty pregnant sows were individually kept in stalls and allocated into two treatment groups using a completely randomized design based on body weight, backfat thickness, and parity. The treatments consisted of either 0% or 0.1% SA supplementation during late gestation and lactation. Following the lactation period, 160 weaned piglets were used to investigate the imprinting effects of SA. The dietary treatment was continued in a manner that the piglets received the same diet as their littermates. Data collected included serum antioxidant status in sows, milk composition, and stress indicators in piglets, measured at various stages. Results Sows fed with SA during late gestation exhibited significantly higher serum total antioxidant status (p<0.03). Additionally, SA supplementation increased lactose content in the milk (p<0.01). Piglets from sows fed the SA diet during late gestation showed lower serum cortisol and epinephrine concentrations at weaning (p<0.01, p<0.04, respectively). SA supplementation during lactation further reduced serum cortisol levels in weaning piglets at one day after weaning (p<0.05). Conclusion The current experiment indicated that supplementing dietary SA in gestation and lactation diet showed higher serum antioxidant properties in sows and improved the quality of sow milk, consequently enhancing litter performance.